Identification of Wolbachia-Responsive miRNAs in the Small Brown Planthopper, Laodelphax striatellus - Liu, Lei; Zhang, Kai-Jun; Rong, Xia; Li, Ya-Ying; Liu, Huai (Frontiers in Physiology, 2019)
Laodelphax striatellus is naturally infected with the Wolbachia strain wStri, which induces strong cytoplasmic incompatibility of its host. MicroRNAs (miRNAs) are a class of endogenous non-coding small RNAs that play a critical role in the regulation of gene expression at post-transcriptional level in various biological processes. Despite various studies have reported that Wolbachia affects the miRNA expression of their hosts, the relationship between them is still very limited. In order to better understand the impact of Wolbachia infection on its host, we investigated the differentially expressed miRNAs between Wolbachia-infected and Wolbachia-uninfected strains of L. striatellus. Compared with uninfected strains, Wolbachia infection resulted in up-regulation of 18 miRNAs and down-regulation of 6 miRNAs in male, while 25 miRNAs were up-regulated and 15 miRNAs were down-regulated in female. The target genes of these differentially expressed miRNAs involved in immune response regulation, reproduction, redox homeostasis and ecdysteroidogenesis were also annotated in both sexes. We further verified the expression of several significantly differentially expressed miRNAs and their predicted target genes by qRT-PCR method, and the results suggested that Wolbachia infection might have many effects on its host. For instance, the results showed that miRNA lst-miR-n21-5p was up-regulated in both Wolbachia-infected females and males, and its predicted target gene, orcokinin (OK, a kind of conserved neuropeptide in arthropods), was down-regulated in both Wolbachia-infected females and males, with especially lower expression level in Wolbachia-infected males. All of the results in this study might contribute to further explore the molecular mechanisms of effects of Wolbachia on its hosts.